EDUKASI OBAT HALAL BAGI PEMUDA MUSLIM DI KAJEN, PEKALONGAN: UPAYA PENINGKATAN LITERASI KESEHATAN BERBASIS SYARIAH - Rafa’at Pasya, Mohammad; Rendi Diki Setiawan, Muhammad; Okta Syahwali, Rengganis; Amalia Rizqi, Nabila; Nova Nuroaftul Aqidah, Nafanda; Hermawan Adinugraha, Hendri (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
The halal pharmaceutical industry is a crucial part of the development of the halal sector in Indonesia, particularly in ensuring that the medicinal products consumed by the public comply with Islamic sharia principles. The issue of halal and haram cannot be considered trivial because it encompasses interpersonal relationships (muamalah) and the relationship between humans and God (ibadah). This study aims to analyze and describe the process of halal drug education for Muslim youth in the Kajen area, Pekalongan, to improve health literacy based on Islamic values. Using qualitative descriptive methods, data were collected through in-depth interviews with 15 respondents, participant observation, and documentation studies. The results indicate that although Muslim youth in the area are aware of the importance of halal drug certification, challenges remain in terms of access to information, limited availability of halal-certified drugs, and a lack of ongoing educational activities. Therefore, the active participation of various parties, including government institutions, religious leaders, and the pharmaceutical industry, is needed to strengthen the halal education system and increase the availability of sharia-compliant drugs.